2015
DOI: 10.1080/02678292.2015.1044576
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of orientation of liquid crystals 5CB and DSCG near surfaces to detect low protein concentration

Abstract: We report the alignment of 4-cyano-4-pentylbiphenyl (5CB), a thermotropic liquid crystal (LC), and disodium chromo glycate (DSCG), a lyotropic LC, on the hydrophobic head group containing dimethyloctadecyl [3-(trimethoxysilyl)propyl]ammonium chloride (DMOAP) and hydrophilic amine head group. Based on the texture observed using a polarised microscope for modified surfaces, we propose the alignment of the LCs on the modified surfaces. It is further supported by Fourier transform infra-red spectroscopy (FTIR) dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…As BSA accumulated at the LC-glass interface, light leakage increased with increasing concentrations of BSA (Figure 4). A similar darkto-bright transition was also reported in the detection of BSA by homeotropically aligned DSCG [34]. However, DSCG tends to reorient from the homeotropic to the planar state over time [35].…”
Section: Lclc-based Spectrometric Quantitation Of Bsasupporting
confidence: 77%
“…As BSA accumulated at the LC-glass interface, light leakage increased with increasing concentrations of BSA (Figure 4). A similar darkto-bright transition was also reported in the detection of BSA by homeotropically aligned DSCG [34]. However, DSCG tends to reorient from the homeotropic to the planar state over time [35].…”
Section: Lclc-based Spectrometric Quantitation Of Bsasupporting
confidence: 77%
“…Typically speaking, the initial alignments of the LC molecules are related to the orientation force provided by the alignment layer at the phase interface. At the LC-solid interface, the alignment layers such as siloxane, aliphatic chain, and oligonucleotides favor the perpendicular alignment of the molecules, [88,89] while the parallel ravine prepared by etching techniques and polyimide (PI) treated by directed rubbing can lead to parallel alignment. [90,91] In addition, at the LC-aqueous interface, the LC alignment can be tuned by varying the components of the aqueous phase.…”
Section: Alignmentsmentioning
confidence: 99%
“…The homeotropic arrangement was that the long axis of 5CB was parallel to the direction of the surface normal, which can be induced by a lecithin layer of hydrophobic surfactant monolayer [13]. Kumar et al [6] found that 5CB aligned homeotropically on both the aminopropyl tri-ethoxy silane (APTES) and dimethyloctadecyl [3-(trimethoxysilyl) propyl] ammonium chloride (DMOAP) surfaces. Fourier transform infrared spectroscopy has confirmed that the C≡N of 5CB interacted with N of APTES and N + of DMOAP [6,17,56].…”
Section: Effect Of Polarity On Molecular Distributionmentioning
confidence: 99%
“…Kumar et al [6] found that 5CB aligned homeotropically on both the aminopropyl tri-ethoxy silane (APTES) and dimethyloctadecyl [3-(trimethoxysilyl) propyl] ammonium chloride (DMOAP) surfaces. Fourier transform infrared spectroscopy has confirmed that the C≡N of 5CB interacted with N of APTES and N + of DMOAP [6,17,56]. Yang et al [57] investigated the interfacial orientation of 5CB supported on salts of metal ions.…”
Section: Effect Of Polarity On Molecular Distributionmentioning
confidence: 99%
See 1 more Smart Citation